2018
DOI: 10.1017/s0022029918000547
|View full text |Cite
|
Sign up to set email alerts
|

LPS-induced reduction of triglyceride synthesis and secretion in dairy cow mammary epithelial cells via decreased SREBP1 expression and activity

Abstract: Sterol regulatory element binding protein 1 (SREBP1) has a central regulatory effect on milk fat synthesis. Lipopolysaccharides (LPS) can induce mastitis and cause milk fat depression in cows. SREBP1 is also known to be associated with inflammatory regulation. Thus, in the current study, we hypothesized that LPS-induced milk fat depression in dairy cow mammary epithelial cells (DCMECs) operates via decreased SREBP1 expression and activity. To examine the hypothesis, DCMECs were isolated and purified from dairy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…TLR4, one of the best characterized TLRs, is a pattern recognition receptor for LPS (Li et al ., 2016; Wang et al ., 2018). TLR4 activates MyD88 and then induces the activation of NF-κB and MAPK signaling pathways to increase the release of pro-inflammatory cytokines (Lu et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…TLR4, one of the best characterized TLRs, is a pattern recognition receptor for LPS (Li et al ., 2016; Wang et al ., 2018). TLR4 activates MyD88 and then induces the activation of NF-κB and MAPK signaling pathways to increase the release of pro-inflammatory cytokines (Lu et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Their cell wall components (endotoxins), including peptidoglycan (PGN), lipoteichoic acid (LTA) and lipopolysaccharide (LPS), are released during the process of proliferation or/and after death. Many previous studies reported that LPS, a pathogen-associated molecular pattern (PAMP), induced inflammatory responses of BMECs, and it could also simultaneously inhibit the proliferation of BMECs [ 23 , 24 , 25 , 26 ] and decrease milk fat synthesis in BMECs by suppressing the expression of fat acid synthesis-related genes [ 4 , 27 , 28 ]. PGN and LTA are also PAMPs that cause inflammatory responses and affect lactation in the mammary gland of cows [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The neurons of newborn mice level were measured by using Ki-67 immunofluorescence. The Ki-67 protein is a cellular marker for proliferation, and it is associated with cell proliferation [28,29]. The results of Ki-67 immunofluorescence imaging indicated that the newborn neurons were significantly less in the cold exposure groups.…”
Section: Discussionmentioning
confidence: 99%